2004
DOI: 10.1111/j.1742-7843.2004.950207.x
|View full text |Cite
|
Sign up to set email alerts
|

Specification of the Structure of Oximes Able to Reactivate Tabun‐Inhibited Acetylcholinesterase

Abstract: The efficacy of various oximes to reactivate acetylcholinesterase phosphorylated by tabun (O-ethyl-N,N-dimethyl phosphoramidocyanidate) was tested by in vitro and in vivo methods. The oximes commonly used for the treatment of acute poisonings with highly toxic organophosphates appeared to be almost ineffective (HI-6, pralidoxime, methoxime) or just slightly effective (obidoxime) against tabun. On the other hand, trimedoxime seemed to be a significantly more efficacious reactivator than the others in the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
95
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 29 publications
3
95
0
Order By: Relevance
“…For example, pralidoxime is unable to reactivate tabun-inhibited and cyclosarin-inhibited AChE in vitro and in vivo [6][7][8]. Similar results were obtained for obidoxime.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…For example, pralidoxime is unable to reactivate tabun-inhibited and cyclosarin-inhibited AChE in vitro and in vivo [6][7][8]. Similar results were obtained for obidoxime.…”
Section: Introductionsupporting
confidence: 72%
“…The chemical structure of AChE reactivators affects their ability to reactivate AChE inhibited by nerve agents [6,8]. Some of the most important moieties include the presence of the oxime group, the presence of quaternary nitrogen, and the appropriate length of the connection chain between both quaternary nitrogens [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aged AChE is inhibited completely and can not be reactivated. One of the most resistant inhibitions is caused by the nerve agent tabun (GA) [18]. Although the structural basis for resistance of tabun conjugates is unknown, the crystal structures of murine AChE showed that non-aged tabun conjugate induces structural changes in H447 and its hydrogen bonds [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, soman inhibited AChE is after several minutes not treatable due to the aging (dealkylation) (5,6). Also AChE inhibited by tabun and cyclosarin is difficult to reactivate due to the lone electron pair at the amide group (tabun) or presence of bulky cyclohexyl group (cyclosarin), respectively (1,7) Currently the most promising AChE reactivator -oxime HI-6 -is not able to reactivate tabun or pesticide-inhibited AChE (1,14).…”
Section: Introductionmentioning
confidence: 99%